Determinants of financial inclusion in Latin America and the Caribbean. Issue 8 (17th November 2022) - Motta, Victor; Gonzalez Farias, Lauro Emilio
ABSTRACT: Financial inclusion is an important determinant of local economic development. Lack of adequate access to formal financial services can have detrimental effects on households, such as hampering liquidity levels. The benefits of financial inclusion could be especially important in Latin America and Caribbean, a region with modest and volatile economic growth, savings, and investment levels. The objective of this paper was to examine the determinants of financial inclusion in Latin America and the Caribbean region. Overall, our results indicate that greater income and education levels are associated with higher probability of financial inclusion.